Development of Storynomics Based on Digital Information Systems as a Medium for Promoting Tourist Attractions - Muhammad Kasim (Journal La Bisecoman, 2023)
This research uses a qualitative research approach, which aims to find out the development of storynomics using English-based digital information systems as a medium for promoting tourist attractions in Majene Regency, as well as how the actual condition of Dato Beach in Majene Regency as a location for making promotional videos of tourist attractions and how human resources for information techniques and English, and how the form of promotion used by the Tourism Office to promote tourist attractions in Majene Regency, West Sulawesi Province. The results showed that the actual condition of Dato Beach as an example of making promotional videos in Majene Regency in order to increase the number of tourist visits after being hit by a global problem, namely the impact of Covid 19. It seems that the government has made promotions in written form in the form of tourist attraction brochures, but the making of Digital-Based storynomics videos has not been implemented, so that the number of tourist visits has not increased, and there are still many tourist attractions that are not yet known by tourists to be visited by both local and foreign tourists, therefore with this storynomics video, hopefully Majene Regency will be better known and the number of tourist visits can increase in the future.